Parliamentary Behavior in the Formation of Local Regulations in Central Maluku - Johan Tehuayo; Syaifulrijal Mahulauw; Fatima Suatrat (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
This study, entitled 'Analysis of Parliamentary Behavior in the Formation of Local Regulations in Central Maluku Regency,' employs a descriptive qualitative method to describe the behavior of DPRD members in their efforts to increase votes and the process of forming local regulations. The research informants consisted of the chair and members of Commission 2, Commission 4, and the Regional Regulation Discussion Agency of the Central Maluku DPRD. This study draws on theories of political behavior, representative democracy, political parties, representative parliaments, legislative elections, and government policy. The results of the study show that candidates actively engage in political interaction with the community through various social and economic programs, such as social assistance, youth empowerment, and improvement of educational facilities, thereby gaining significant support and seats in the DPRD. The deliberation process for local regulations proceeded in accordance with the procedures stipulated by the Minister of Home Affairs Regulation, with maximum public participation through seminars involving various stakeholders from the sub-districts. The resulting local regulations have strong legal force and a positive impact on the community, the business world, and an increase in Local Own-Source Revenue. The DPRD's supervision of the implementation of local regulations is carried out effectively and to the maximum extent possible, supporting the successful implementation of various local regulations in Central Maluku.